2021
DOI: 10.1038/s41598-021-85583-x
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative partner choice in multi-level male dolphin alliances

Abstract: Investigations into cooperative partner choice should consider both potential and realised partners, allowing for the comparison of traits across all those available. Male bottlenose dolphins form persisting multi-level alliances. Second-order alliances of 4–14 males are the core social unit, within which 2–3 males form first-order alliances to sequester females during consortships. We compared social bond strength, relatedness and age similarity of potential and realised partners of individual males in two ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 80 publications
1
12
0
Order By: Relevance
“…Coalition formation, defined as cooperation in an aggressive or competitive context, where one animal intervenes in an ongoing conflict between two parties to support one side (Harcourt and de Waal, 1992), is one of the notable alternative tactics in males to improve their dominance-based status, which improves their mating success (Noë and Sluijter, 1990). Coalition formation in males has been reported in various mammalian taxa, e.g., cetaceans (Diaz-Aguirre et al, 2018;Gerber et al, 2021) and carnivores (Packer et al, 1991;Caro and Collins, 2010), although it has most extensively been studied in primates (van Schaik et al, 2006). Nonetheless, at present, we lack a comprehensive understanding of the proximate mechanisms underlying such cooperative coalition behaviors, i.e., who helps whom (Rodrigues and Kokko, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Coalition formation, defined as cooperation in an aggressive or competitive context, where one animal intervenes in an ongoing conflict between two parties to support one side (Harcourt and de Waal, 1992), is one of the notable alternative tactics in males to improve their dominance-based status, which improves their mating success (Noë and Sluijter, 1990). Coalition formation in males has been reported in various mammalian taxa, e.g., cetaceans (Diaz-Aguirre et al, 2018;Gerber et al, 2021) and carnivores (Packer et al, 1991;Caro and Collins, 2010), although it has most extensively been studied in primates (van Schaik et al, 2006). Nonetheless, at present, we lack a comprehensive understanding of the proximate mechanisms underlying such cooperative coalition behaviors, i.e., who helps whom (Rodrigues and Kokko, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Greater participation by male WSR dolphins suggests that mating opportunities may play a role in mixed group formation, as in bonobos [ 68 ]. Spotted dolphins’ fission–fusion grouping also renders male defence of females impossible except possibly for short periods, as occurs in some bottlenose dolphins [ 53 ], whose non-kin, strategic alliances are largely developed among similar age peers that associated as juveniles [ 70 , 71 ]. The formation of male–male bonds among previously unfamiliar spotted dolphins suggests a similar strategic flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that the partner choice in coalitions is related to social relationships and rank. Males choose the coalition that works best for them according to different situations [ 36 , 37 , 38 ]. In semi-free-ranging Barbary macaques, males are more likely to support maternal relatives than non-relatives, and kinship plays an important role in coalition decision-making [ 39 ].…”
Section: Discussionmentioning
confidence: 99%